2018
DOI: 10.1016/j.healun.2017.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant mitral valve procedures in patients undergoing implantation of continuous-flow left ventricular assist devices: An INTERMACS database analysis

Abstract: Concomitant MVPs are not associated with increased survival overall. However, MVPs are associated with benefits in terms of reduced hospital re-admission and improved quality of life in select patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 19 publications
1
65
0
Order By: Relevance
“…There have been several prior small studies, although mostly uncontrolled, some suggesting a role for mitral surgery and others suggesting it is unnecessary. A recently published large multicenter analysis based on Interagency Registry for Mechanically Assisted Circulatory Support data included more than 250 mitral valve procedures and found lesser hospitalizations and improved functional status in patients who have MVr, 16 thus supporting our findings. However, all these studies have been retrospectively analyzed.…”
Section: Future Directionssupporting
confidence: 87%
“…There have been several prior small studies, although mostly uncontrolled, some suggesting a role for mitral surgery and others suggesting it is unnecessary. A recently published large multicenter analysis based on Interagency Registry for Mechanically Assisted Circulatory Support data included more than 250 mitral valve procedures and found lesser hospitalizations and improved functional status in patients who have MVr, 16 thus supporting our findings. However, all these studies have been retrospectively analyzed.…”
Section: Future Directionssupporting
confidence: 87%
“…3−6 In registry analyses, concomitant mitral valve (MV) procedures have been associated with reduced hospitalizations and better quality of life but not improved survival. 3 Other multicenter studies have pointed to a survival benefit in those with uncorrected severe MR at baseline. 4 However, single-center studies have demonstrated that post-LVAD implantation residual MR may adversely impact hemodynamics and right ventricular function, whereas others have suggested resolution of severe MR in most cases after LVAD implantation.…”
mentioning
confidence: 98%
“…11 Recently, the INTERMACS registry failed to demonstrate a survival benefit in LVAD patients receiving concomitant MVS. 12 Does concomitant MVS really have no clinical benefit? In this study, we focused on hemodynamic profile and reconsidered the implication of concomitant MVS at LVAD implantation.…”
mentioning
confidence: 99%